Successful Allogeneic Hematopoietic Stem Cell Transplantation in XIAP Deficiency Using Reduced‐Intensity Conditioning. Issue 2 (23rd September 2015) - Chellapandian, Deepak; Krueger, Joerg; Schechter, Tal; Gassas, Adam; Weitzman, Sheila; Naqvi, Ahmed; Ali, Muhammad
Abstract : Hematopoietic stem cell transplantation (HSCT) is currently the only available curative therapy for X‐linked inhibitor of apoptosis (XIAP) deficiency. Myeloablative conditioning regimens are associated with high mortality rates. Reduced‐intensity conditioning (RIC) is recommended in order to decrease treatment‐related toxicities, but RIC regimens increase the risk for mixed donor‐recipient chimerism that may progress to graft loss. We report our experience with a patient with XIAP deficiency who was successfully treated with allogeneic HSCT using a RIC protocol. Post‐transplant chimerism was vigilantly monitored and maintained with donor lymphocyte infusions and a stem cell boost to a level that prevented hemophagocytic lymphohistiocytosis recurrence. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.